In relation to determination of the essence of concept «defence of public moral» - Новицька, Наталія Борисівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
The article deals with administrative and legal mechanism to protect public morals and defined the essence of the concept of «defence of public morality».